The Role of Genetically Determined Glycemic Traits in Breast Cancer: A Mendelian Randomization Study - Jung, Su Yon; Mancuso, Nicholas; Han, Sihao; Zhang, Zuo-Feng (Frontiers in Genetics, 2020)
Background Circulating glycemic traits (GTs) have been considered a risk factor for breast cancer, but studies using GT-associated genetic variants as an instrumental variable are limited and inconclusive. Methods Our Mendelian Randomization analysis used the most recent genome-wide datasets focusing on European women. Results Of 44 single-nucleotide polymorphisms (SNPs) with GTs, 38 fasting-glucose and 6 fasting-insulin SNPs showed heterogeneous associations with breast cancer, without significant directional pleiotropy observed. Conclusion Our findings indicate a null association between genetically determined GTs and breast cancer risk among European women. Our findings may contribute to more complete characterizing of metabolic pathways in GTs and breast cancer.